Prevalence and predictors of overweight and obesity among Cameroonian women in a national survey and relationships with waist circumference and inflammation in Yaoundé and Douala. Issue 4 (26th July 2018) - Engle‐Stone, Reina; Nankap, Martin; Ndjebayi, Alex O.; Friedman, Avital; Tarini, Ann; Brown, Kenneth H.; Kaiser, Lucia
Abstract: Information on the distribution and predictors of obesity in Africa is needed to identify populations at risk and explore intervention options. Our objectives were to (a) examine the prevalence and geographic distribution of overweight and obesity among Cameroonian women; (b) evaluate change in anthropometric indicators among urban women between 2009 and 2012; (c) examine associations between household and individual characteristics and overweight and obesity; and (d) examine relationships between body mass index (BMI), abdominal obesity, and inflammation. We analysed data from a nationally representative survey conducted in 3 geographic strata (North, South, and Yaoundé/Douala) in Cameroon in 2009 and a survey in Yaoundé/Douala in 2012. Participants selected for this analysis were nonpregnant women, ages 15–49 years ( n  = 704 in 2009; n  = 243 in 2012). In 2009, ~8% of women were underweight (BMI < 18.5) and 32% overweight or obese (BMI ≥ 25.0). Underweight was most common in the North (19%) and overweight and obesity in the South (40%) and Yaoundé/Douala (49%). Prevalence of BMI ≥ 25.0 in Yaoundé/Douala did not differ in 2012 compared with 2009 (55.5% vs. 48.7%; P  = 0.16). Residence in urban areas, greater maternal age, and TV ownership were independently related to overweight and obesity in national and stratified analyses. In Yaoundé/Douala in 2012, 48% (waist‐to‐hip ratio > 0.85) to 73% (waist circumference > 80 cm) had abdominal obesity. Body mass index was positively associated with abdominal obesity and inflammation. Though causal inferences cannot be drawn, these findings indicate population subgroups at greatest risk for overweight and associated health consequences in Cameroon.